2014
DOI: 10.3390/ijms15011418
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarkers of Acute Stroke

Abstract: MicroRNAs have been identified as key regulators of gene expression and thus their potential in disease diagnostics, prognosis and therapy is being actively pursued. Deregulation of microRNAs in cerebral pathogenesis has been reported to a limited extent in both animal models and human. Due to the complexity of the pathology, identifying stroke specific microRNAs has been a challenge. This study shows that microRNA profiles reflect not only the temporal progression of stroke but also the specific etiologies. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 30 publications
5
114
2
4
Order By: Relevance
“…Hundreds of genes may have an impact on stroke pathogenesis or are associated with risk factors [8]. However, their specificity and ability to distinguish among different phases of stroke, especially the hyperacute phase, or symptoms resembling stroke is uncertain [9]. Therefore, we attempted to seek a biomarker for the diagnosis of hyperacute IS, analogous to troponin in the assessment of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of genes may have an impact on stroke pathogenesis or are associated with risk factors [8]. However, their specificity and ability to distinguish among different phases of stroke, especially the hyperacute phase, or symptoms resembling stroke is uncertain [9]. Therefore, we attempted to seek a biomarker for the diagnosis of hyperacute IS, analogous to troponin in the assessment of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of miR-125b-2*, miR-27a*, miR-422a, miR-488 and miR-627 were consistently observed in patients with acute stroke, irrespective of age, severity, or confounding metabolic complications. The same five miRNAs were also upregulated in a rat model of middle cerebral artery occlusion, further supporting that the change in expression was as a result of acute cerebral ischemia [38].…”
Section: Mirna In Cerebrovascular Diseasesmentioning
confidence: 57%
“…Ischemic brain injury has been shown to change expressions of miRNA in animal models of cerebral ischemia and in stroke patients, suggesting that miRNAs are involved in the early stress response to ischemic insult to the brain [36,37]. Sepramaniam et al demonstrated that stroke patients have specific miRNAs expression that can distinguish stroke subtypes [38]. Upregulation of miR-125b-2*, miR-27a*, miR-422a, miR-488 and miR-627 were consistently observed in patients with acute stroke, irrespective of age, severity, or confounding metabolic complications.…”
Section: Mirna In Cerebrovascular Diseasesmentioning
confidence: 99%
“…Since many [71]. In stroke field, increased or decreased levels of several circulating microRNA were reported in isch emic stroke patients [72,73]. For example, microRNA424 lev el was decreased in acute stroke patients and in an animal model of stroke, and intracerebroventricular injection of len tiviral microRNA424 reduced ischemic brain injury [72].…”
Section: Micrornasmentioning
confidence: 99%